THE INTEGRATION OF TECHNOLOGY, ENTREPRENEURSHIP, AND ACCOUNTING: PILLARS OF SUSTAINABLE BUSINESS FOR GENERATION Z - Komari, Ghulam; Churin Oktavia; Islamiati Hidayah (Al-Muhasib: Journal of Islamic Accounting and Finance, 2024)
Abstract: This article analyzes the potential of Generation Z in technology-based entrepreneurship. With high digital skills and interest in social issues, this generation has great potential. However, challenges such as capital access and tight competition must be overcome. Integration of technology, entrepreneurship, and accounting is the key to success. This study highlights the importance of the role of education, environment, and philanthropy in supporting the growth of young generation entrepreneurship. The concept of Islamic Philanthropy is proposed as a foundation for sustainable businesses that do not only pursue profit, but also provide social benefits. Abstrak: Artikel ini menganalisis potensi Generasi Z dalam bidang entrepreneurship berbasis teknologi. Dengan keterampilan digital yang tinggi dan ketertarikan terhadap isu-isu sosial, generasi ini memiliki potensi yang besar. Namun, tantangan seperti akses modal dan persaingan yang ketat perlu diatasi. Integrasi teknologi, kewirausahaan, dan akuntansi adalah kunci keberhasilan. Studi ini menyoroti pentingnya peran pendidikan, lingkungan, dan filantropi dalam mendukung pertumbuhan kewirausahaan generasi muda. Konsep Filantropi Islam diusulkan sebagai landasan untuk bisnis berkelanjutan yang tidak hanya mengejar keuntungan, tetapi juga memberikan manfaat sosial.